2015
DOI: 10.1088/0031-9155/60/19/7763
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of evaluating tumor vascularization using 3D power Doppler ultrasound with high-definition flow technology in the prediction of the response to neoadjuvant chemotherapy for T2 breast cancer: a preliminary report

Abstract: Institute of Physics and Engineering in MedicineContent from this work may be used under the terms of the Creative Commons Attribution 3.0 licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Combining the pathology data (histology, grade, tumor biomarker expression) with sonography or mammography features, or adding additional imaging features to improve the predictive accuracy is a well‐known approach and has demonstrated a good prediction performance . However, the acquisition of pathology data and assessment of additional image features requires further analysis, as this can be labor‐intensive work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining the pathology data (histology, grade, tumor biomarker expression) with sonography or mammography features, or adding additional imaging features to improve the predictive accuracy is a well‐known approach and has demonstrated a good prediction performance . However, the acquisition of pathology data and assessment of additional image features requires further analysis, as this can be labor‐intensive work.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the pathology data (histology, grade, tumor biomarker expression) with sonography or mammography features, or adding additional imaging features to improve the predictive accuracy is a well-known approach and has demonstrated a good prediction performance. 26,27 However, the acquisition of pathology data and assessment of additional image features requires further analysis, as this can be labor-intensive work. In this study, the analysis was simply based on the variation of fundamental vascular flow indices, and our preliminary results show that these variations provide sufficient information to directly improve the observation of the chemotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Further development of integrating this technology with 3-D ultrasound imaging can enhance the accuracy and reliability in the assessment of intranodal vascularity. Previous studies on analysis of the VI of breast cancer in 3-D ultrasound found that intra-tumour VI is useful in the evaluation of prognosis and treatment response of breast cancer patients (26,27). Recent superb microvascular imaging (SMI) technology allows for detection of microvascularity.…”
Section: A B Cmentioning
confidence: 99%
“…Due to the signal sensitivity to noise in small vessels and the sensitivity to the motion of tissue, accurate extraction of complex vasculature using power Doppler is challenging. In most of the studies using power Doppler, blood vessels are usually segmented by thresholding [3][4][5] . However, the unavoidable noise during imaging means using just a simple thresholding method may not be robust enough.…”
Section: Introductionmentioning
confidence: 99%